Biomarkers Can Identify Pulmonary Tuberculosis in HIV-infected Drug Users Months Prior to Clinical Diagnosis - Rosa Sloot; Maarten F. Schim van der Loeff; Erik W. van Zwet; Mariëlle C. Haks; Sytze T. Keizer; Maarten Scholing; Tom H.M. Ottenhoff; Martien W. Borgdorff; Simone A. Joosten (EBioMedicine, 2015)
Background: Current diagnostic tests cannot identify which infected individuals are at risk for progression to tuberculosis (TB). Our aim was to identify biomarkers which can predict the development of TB prior to clinical diagnosis. Method: In a retrospective case–control study, RNA of 14 HIV-infected drug users obtained before TB diagnosis (cases) and of 15 who did not develop TB (controls) was analyzed for the expression of 141 genes by dcRT-MLPA followed by Lasso regression analysis. Findings: A combined analysis of IL13 and AIRE had the highest discriminatory power to identify cases up to 8 months prior to clinical diagnosis. Cases expressing IL13 had a gene expression pattern strongly enriched for type I IFN related signaling genes, suggesting that these genes represent processes that contribute to TB pathogenesis. Interpretation: We here demonstrated that biomarkers, such as IL13-AIRE, can identify individuals that progress to TB within a high risk population, months prior to clinical diagnosis.